Ethnopharmacological survey of herbal remedies used for treatment of various types of cancer and their methods of preparations in the West Bank-Palestine - Jaradat, Nidal Amin (BMC Complement Altern Med, 2016)
BACKGROUND: Plants have been the primary source of medicines since life on earth; more than 50 % of existing cancer treatments are derived from plants. METHODS: An ethnopharmacological survey of herbal remedies used in cancer treatment was carried out in the West Bank/ Palestine. A questionnaire was distributed to one hundred and fifty herbalists, traditional healers and rural dwellers. Collected information included the names of plants, the used parts, types of cancers for which these plants were used and also their methods of preparation. To identify the most important species used, Factor of informant’s consensus (F(ic)), Fidelity level (Fl) and the Use-value (UV) were calculated. RESULTS: Collected data has shown that 72 plants are utilized for treatment of cancer, belonging to 44 families; from them Compositae and Lamiaceae were the most common. Leaves and fruits were the most commonly used parts, while decoctions, infusions and syrups were the main methods of preparation. Lung cancer was the most common type of cancer treated with these plants and Ephedra alata was the most commonly used plant for treatment of cancer in Palestine. The F(ic) was high for all the plants; Fl was 100 % for many plants, the highest UV (0.72) was for Ephedra alata. CONCLUSIONS: This study showed that many herbal remedies are still used by herbalists in Palestine for treatment of cancer; some of them have been approved scientifically while others are not. A combined effort between informants and scientific institutions working in this field can help in the discovery of new anticancer agents. Moreover, scientists must explore the most suitable method of extraction, formulation and dose determination in order to achieve the best benefits from these herbals.